Problematika Mahasiswa Dalam Menulis Karya Ilmiah - Rahmiati, Rahmiati (Jurnal Adabiyah, 2013)
There is no doubt that writing is among the important skills ones have to possess in order to be able express themselves. People are able to communicate their ideas and opinion through the medium of writing as an alternative to oral medium. The challenge is that several key issues prohibit people, including students from writing effectively. This is particularly the case with academic writing. This article outlines several key impediments students encounter in academic writing. This analysis is undertaken on the basis of review of the existing literature and the writerâs own reflections of teaching academic writing skills for students in higher education context. Among the key inhibitors faced by students in academic writing are lack of motivation, lack of ideas to write, limited opportunities to practice academic writing, and lack of support, recognition and appreciation from authorities.Â Â Â